Determining the optimal sampling method to estimate the mean and standard deviation of pig body weights within a population - Chad B Paulk; Michael D Tokach; Steven S Dritz; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2014)
The accuracy and precision of pig subsampling methods can determine the swine producer's ability to sell pigs at optimal market BW and reduce economic discounts. The first objective of this experiment was to determine the time required to weigh pigs for different sampling methods used to estimate the mean and SD of a population. The second objective was to define the optimal sampling method considering the time required to weigh pigs as well as the precision and accuracy of each sampling method. A total of 68 pens of pigs (359 × 1050, PIC, Hendersonville, TN; 169.8 lb BW) in 2 commercial finishing facilities with 20 to 35 pigs per pen were used. Pens of pigs were blocked by location within barn and randomly allotted to 1 of 4 treatments with 17 pens per treatment. The 4 treatments included (1) selecting and weighing the heaviest and lightest pig per pen; and (2), (3), and (4) weighing the first 5, 10, and 15 pigs out of the pen, respectively. The time required for 2 people to complete each treatment was recorded. To determine the total barn time required to conduct a specific sample, the time required to weigh the specific number of pigs per pen was multiplied by n pens. The accuracy and precision for estimating the mean BW and SD for each sampling method was determined by using datasets A and C reported in Paulk (20144). The precision was determined by calculating a 95% confidence interval (CI) for the sample means and SD. The time taken to select and weigh the heaviest and lightest pigs in a pen (Treatment 1) did not differ from weighing 5 pigs per pen (Treatment 2). Increasing the number of pigs weighed per pen (Treatments 3 and 4) increased (P<0.05) the amount of time to weigh a single pen. Based on these results, the number of pens for each treatment that can be weighed without influencing weighing time was determined to be 15 pens (30 pigs), 15 pens (75 pigs), 9 pens (90 pigs), and 6 pens (90 pigs) from Treatments 1, 2, 3, and 4, respectively. For dataset A, these 4 sampling methods had a similar CI range for estimating the mean BW and SD. For dataset C, Treatments 1 (30 pigs) and 2 (75 pigs) had a reduced CI range for estimating the mean BW compared with Treatments 3 (90 pigs) and 4 (90 pigs); however, Treatments 2 (75 pigs) and 3 (90 pigs) had a reduced CI range for estimating the SD compared with Treatments 1 (30 pigs) and 4 (90 pigs). Therefore, we conclude that swine producers should weigh 5 pigs from 15 pens to estimate the mean BW and SD within a barn.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Finishing pig; Mean estimation; Standard deviation estimation; Sample size